1989
DOI: 10.1007/bf00144842
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors in congenital heart disease

Abstract: Risk factors were studied in 801 children with congenital heart disease (CHD) coming from 105,374 consecutive births of known outcome. The incidence of CHD was 7.60%. Diagnosis was performed in 66.5% of the cases during the perinatal period. Two-hundred-fifty seven of the cases also had at least one non-cardiac malformation (multiply malformed). Ninety-two cardiac infants (11.47%) had recognized chromosomal and non-chromosomal syndromes. The most frequent noncardiac malformations were renal, digestive and limb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
45
1
8

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(58 citation statements)
references
References 15 publications
4
45
1
8
Order By: Relevance
“…37 A number of studies have assessed the association between CHD and measures of prenatal cerebral growth including fetal MRI studies, 7 prenatal ultrasound measurements, 13 and head circumference at birth. 15 With few exceptions, 19,38 all studies found an association between CHD and smaller measures of prenatal cerebral growth. Because of small sample sizes some studies were forced to treat CHD as a single entity 7 or applied less well-defined subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…37 A number of studies have assessed the association between CHD and measures of prenatal cerebral growth including fetal MRI studies, 7 prenatal ultrasound measurements, 13 and head circumference at birth. 15 With few exceptions, 19,38 all studies found an association between CHD and smaller measures of prenatal cerebral growth. Because of small sample sizes some studies were forced to treat CHD as a single entity 7 or applied less well-defined subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of chromosomal abnormalities reported in subsets of patients from other studies ranged from 2.6 to 12.5% (usually around 9%) 7,8,[18][19][20][21][22][23]25,26,29,30 . Our study detected the highest rate (14.6%) and was the only one to perform karyotype analysis in all patients and to specifically assess this approach.…”
Section: Discussionmentioning
confidence: 90%
“…The urinary tract malformations were also prevalent in the study of Bosi et al 22 , Stephensen et al 25 , Amorim et al 28 and Gonzalez et al 9 . Genitourinary tract abnormalities were found from 7.4 to 15.1% of patients with CHD in different series 18,20,24,26 and in 15.2% of live births and in 25.3% of stillbirths in the study of Amorim et al 28 . Kramer et al 19 , using postangiography urography, found 8.9% of upper urinary tract abnormalities in 302 patients with CHD.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations